Influence of copper slag and GGBS on mechanical properties of concrete. Issue 1 (March 2021) - Rahmathulla Noufal, E; Kasthurba, A K; Sudhakumar, J
Abstract: The construction industry consumes a huge amount of concrete due to fast urbanization and an increase in the construction field is depleting the resources of natural sand and M sand at a high rate of concern hence leading to various problems in the environment. Besides that, cementitious material in concrete releases a large amount of CO2 into atmosphere. Similarly cost of concrete is attributed to the cost of its ingredients. The concept of using eco-friendly materials in concrete enhances scope for green concrete which utilizes many kinds of industrial by-products thus resulting in the use of substitute materials which are economical in concrete production. This has attracted the attention of investigators to look out for new replacements for fine aggregate and cement. At this degree, copper slag, which is an industrial by-product produced while smelting and refining copper may be a partial alternative for fine aggregate and GGBS, a by-product of steel manufacturing industry can effectively replace cement with better durable concrete mix. Thereafter, an attempt has been made to control the cost of cement and sand with concrete blend of grade M25&M30 through methodical evaluation of physical, mechanical and chemical properties in the present work. Series of concrete mixtures are prepared with a constant 40% copper slag substituting fine aggregate and GBBS replaces cement at 0%, to 50% with5% increment. The results suggest that copper slag and GGBS can replace fine aggregate and cement in reinforced cement concrete, without compromising on the quality, thereby contributing to the effort of environment friendly building materials with economic benefits, which is the need of the hour.